IL‐6–induced cGGNBP2 encodes a protein to promote cell growth and metastasis in intrahepatic cholangiocarcinoma. Issue 6 (21st December 2021) - Li, Hui; Lan, Tian; Liu, Hailing; Liu, Chang; Dai, Junlong; Xu, Lin; Cai, Yunshi; Hou, Guimin; Xie, Kunlin; Liao, Mingheng; Li, Jiaxin; Huang, Jiwei; et al.
Abstract: Background and Aims: IL‐6–induced tumor progression has been well established through the induction of antiapoptotic and proliferative genes. However, whether other mechanisms such as IL‐6 regulation of circular RNAs (circRNAs) may also contribute to tumor development remains unknown. Approach and Results: High‐throughput RNA sequencing was used to identify the differentially expressed circRNAs on IL‐6 stimulation in intrahepatic cholangiocarcinoma (ICC) cells. CircRNA GGNBP2 (derived from ggnbp2 gene, termed as cGGNBP2) was up‐regulated by IL‐6 treatment in a time and concentration‐dependent manner. The biogenesis of cGGNBP2 was regulated by RNA‐binding protein DEx‐H Box Helicase 9, which was also mediated by IL‐6 exposure. Mass spectrometry and western blotting identified a protein cGGNBP2‐184aa encoded by cGGNBP2. cGGNBP2‐184aa promoted ICC cell proliferation and metastasis in vitro and in vivo. Mechanistically, cGGNBP2‐184aa directly interacted with signal transducers and activators of transduction‐3 (STAT3), phosphorylated STAT3 Tyr705, and played a positive regulatory role in modulating IL‐6/STAT3 signaling. IL‐6/cGGNBP2‐184aa/STAT3 formed a positive feedback loop to sustain constitutive activation of IL‐6/STAT3 signaling. Elevated cGGNBP2 expression was correlated with poor prognosis of patients with ICC and was identified as an independent risk factor for patient prognosis. Conclusions: Our study demonstrates that cGGNBP2‐184aa, a protein encoded by IL‐6–induced cGGNBP2, formed a positive feedback loop to facilitate ICC progression and may serve as an auxiliary target for clinical IL‐6/STAT3‐targeting treatments in ICC.